An overview of the Australian psolid sea cucumbers (Echinodermata: Holothuroidea: Psolidae) with the description of 5 new species - Mackenzie, Melanie; Whitfield, Emily (Zootaxa, 2011)
Four new species of Psolus Oken from Australia are described: Psolus parantarcticus sp. nov. from Macquarie Island, Psolus salottii sp. nov. from South Australia and Macquarie Island, Psolus steuarti sp. nov. from Victoria, and Psolus springthorpei sp. nov. from Queensland. One new species of Psolidium Ludwig from Australia is described: Psolidium oloughlini sp. nov. from King Island. All Australian psolid species are included in the overview: Ceto cuvieria (Cuvier), Psolidium berentsae O’Loughlin & Maric, P. granuliferum H.L. Clark, P. hutchingsae O’Loughlin & Maric, P. karenae O’Loughlin & Maric, P. laperousazi O’Loughlin & Maric, P. marshae O’Loughlin & Maric, P. mccallumae O’Loughlin & Maric, P. minutum (H.L. Clark), P. nigrescens H.L. Clark, P. parmatum (Sluiter), P. ravum Hickman, P. spinuliferum (H.L. Clark), and Psolus antarcticus (Philippi). A key to the Australian species of Psolidae is provided.